2022
DOI: 10.23887/jere.v6i4.48090
|View full text |Cite
|
Sign up to set email alerts
|

Improving Critical Thinking Skill Through Team-based Projects, is it Effective?

Abstract: Facing the 21st-century learning era, critical thinking skills are very important for students and become one of the goals of education in higher education. To achieve one of these educational goals, learning is needed that can form critical, innovative, creative, and competitive students. This study aims to improve students' critical thinking skills on materials for developing rural and urban areas in a sustainable manner in wetlands, through a team-based project learning model. This research uses a pre-exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The findings presented in this paper are in line with the views of modern re-searchers in educational evaluation (Al Mamun et al, 2022;Aristin & Purnomo, 2022). Similarly, previous study argue that the assessment of the student's performance from a pedagogical perspective should aim at taking appropriate pedagogical measures, which will contribute to reaching pedagogical and didactic goals, encourage and strengthen the student, and upgrade the overall learning processes (Amri & Alasmari, 2021;Nelson et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…The findings presented in this paper are in line with the views of modern re-searchers in educational evaluation (Al Mamun et al, 2022;Aristin & Purnomo, 2022). Similarly, previous study argue that the assessment of the student's performance from a pedagogical perspective should aim at taking appropriate pedagogical measures, which will contribute to reaching pedagogical and didactic goals, encourage and strengthen the student, and upgrade the overall learning processes (Amri & Alasmari, 2021;Nelson et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…However, no research has been found on the application of the Level of Inquiry model combined with Project Learning to increase the creativity of PPTs. Project-based learning has much potential for enhancing 21st-century skills and engaging students in real-world tasks (Aristin & Purnomo, 2022 Haatainen & Aksela, 2021). The main components of Project-Based Learning are (1) asking questions or problems to organize and start activities and (2) obtaining the final result or several products as a series of activities, individual communication, or various task results that answer the problem (W. S. Dewi et al, 2022;Made et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have stated that project-based learning (PjBL) is useful in improving problem solving (Jaenudin et al, 2020;Karan & Brown, 2022), critical thinking (Aristin & Purnomo, 2022;Desiana et al, 2022), creative thinking (Cahyani, 2021;Handayani et al, 2023;Jaenudin et al, 2020), and innovative thinking (Artama et al, 2023;Asbjornsen, 2015). However, most PjBL research is still implemented individually, and there is no technology integration.…”
mentioning
confidence: 99%